Politeness Principles Used by EFL Teachers in Classroom Interaction during Teaching-Learning Process - Ratnasari Dewi; Bahrun Amin; Nur Qalbi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Politeness is one of the main factors to achieve character education. The teacher should pay attention, show politeness, and consider themselves as part of parents. The purpose is to make some middle school teachers recognize how to criticize appropriately. This research was carried out to identify the types of politeness principles used by the EFL teachers during the classroom interaction, andto find out the effects of politeness principles in the classroom interaction during teaching-learning process. The researcher has chosen English teacher on the seventh and eighth grade at Lab School of UNISMUH Makassar. The researcher joined in the class and recorded the activities when teachers were teaching. The researcher applied descriptive qualitative method to analyze the data, by doing data reduction, data display and conclusion. The researcher used the theory of politeness by Geoffrey Leech (2016) about politeness principle, which consists of six maxims, namely tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The result of the observation showed that the EFL teachers used five maxims, namely tact maxim, generosity maxim, approbation maxim, agreement maxim, and sympathy maxim.Furthermore, the results of the interviews showed that the principle of politeness could create togetherness between teachers and students, build respect for students, create cooperative interactions between teachers and students, help students to have positive feelings towards lessons, motivate them to participate actively in class and also shapes the character and self-development of students to local culture.